Caracterização molecular de Giardia duodenalis em amostras fecais humanas de dois municípios do noroeste paulista - Santos Junior, Juares Elias (2010)
The parasite Giardia duodenalis, responsible for giardiasis, is commonly found in intestines of mammals, including man, currently considered to be important public health. Molecular research showed that G. duodenalis presents seven genotypes: A, B, C, D, E, F and G. Only genotypes A, which owns the subgenotypes A1 and A2 and B were detected in humans but also in other mammalian hosts. Objective: Evaluate the genotypic frequency of this parasite in humans in the Northwest region and to correlate the presence of diarrhea and their genotypes. Material and Method: Fecal samples were collected in the city of São José do Rio Preto (n = 150) and Araçatuba (n = 154), Northwest of São Paulo, Brazil. The parasitologic diagnosis was done by light microscopy and genotyping of β-Giardin gene by PCR-RFLP. Results: The subgenotype A1 was the most prevalent, however, the subgenotype A2 more frequent in Araçatuba. Genotype B was not found. No significant result was observed between significant stool consistency and subgenotype detected. Conclusion: The distribution of these genotypes may be related to host-parasite interactions in several areas and may influence the clinical and epidemiologic each region.